Transcriptome sequencing and functional analysis reveal RrCBF genes as key regulators of cold adaptation in Rosa rugosa - Guo, Dongliang; Zhao, Mengqi; Yang, Yang; Li, Yushan; Zhu, Leilei; Li, Feifei; Jiang, Haixia; Xu, Lin; Xie, Liqiong (Frontiers in Plant Science, 2025)
Rosa rugosa is an economically significant ornamental species with limited understanding of its molecular cold adaptation mechanisms. This study utilized transcriptome sequencing to elucidate the temporal dynamics and organ-specific regulatory mechanisms underlying cold stress (4°C) responses in the leaves and one-year-old stem of R. rugosa. Differential gene expression analysis revealed distinct organ-specific and time-dependent transcriptional reprogramming. A core set of 1,479 and 1,872 genes were consistently differentially expressed from early to late stages (4–24 h) in leaves and stems, respectively. Intersection analysis identified 1,550 conserved early cold-responsive genes shared between two R. rugosa cultivars. These genes were significantly enriched in the MAPK signaling pathway, plant hormone signal transduction, cytoskeleton-related processes, and metabolic reprogramming. Weighted gene co-expression network analysis (WGCNA) pinpointed RrCBFs as central hubs. Genome-wide characterization identifies five RrCBF genes in R. rugosa as cold-inducible central regulators, universally upregulated under cold stress despite divergent cis-elements. Heterologous overexpression of RrCBF1/RrCBF5 in Arabidopsis enhanced freezing tolerance through reduced oxidative damage, improved osmoprotection, and stabilized photosystem function. Critically, transgenic lines exhibited pleiotropic developmental alterations: dwarfism, delayed flowering, and suppressed vegetative-reproductive transition, indicating trade-offs between growth and stress adaptation. Our results delineate a CBF-centric regulatory module coordinating antioxidant defense, photosynthetic protection, and developmental plasticity in R. rugosa cold adaptation, providing targets for cold-tolerance breeding.